2004
DOI: 10.1021/es049277f
|View full text |Cite
|
Sign up to set email alerts
|

Lead Isotopes in Lichen Transplants around a Cu Smelter in Russia Determined by MC-ICP-MS Reveal Transient Records of Multiple Sources

Abstract: Transplants of the lichen Hypogymnia physodes, which is relatively tolerant to SO2 and heavy metals, were deployed for 3 months over a 60 km long SW-NE transect centered on a highly polluting Cu smelter and its adjoining town of Karabash, southern Urals, Russia. The abundance of 206Pb, 207Pb, 208Pb, and 204Pb were determined by MC-ICP-MS. The measurement of 204Pb revealed critical features, which would otherwise remain concealed: (i) The precise isotope ratios referenced to 204Pb allowed several different sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 26 publications
2
25
0
Order By: Relevance
“…6) already contained a component from both the blast furnace and converter and that over the 2 or 3 month transplantation experiment there is a net loss of smelter-derived components. This strengthens, and broadens the finding of Spiro et al (2004), using Pb isotopes for the same lichen material, that over the sampling period the Pb-containing components in the transplants from the control site were replaced. Lichen transplants may therefore provide a transient record reflecting a continuous gain and loss of environmental Pb, as well as other mining-related metals.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…6) already contained a component from both the blast furnace and converter and that over the 2 or 3 month transplantation experiment there is a net loss of smelter-derived components. This strengthens, and broadens the finding of Spiro et al (2004), using Pb isotopes for the same lichen material, that over the sampling period the Pb-containing components in the transplants from the control site were replaced. Lichen transplants may therefore provide a transient record reflecting a continuous gain and loss of environmental Pb, as well as other mining-related metals.…”
Section: Discussionsupporting
confidence: 69%
“…This study is an extension of work on the same sample set by Purvis et al (2004Purvis et al ( , 2006 and Spiro et al (2004). However emphasis is placed on identifying and apportioning the main sources of elements in the transplants, indicative of miningrelated activities.…”
mentioning
confidence: 99%
“…Lead isotopes can enhance the quality of information deduced from biomonitoring. Lead isotopic abundances in geogenic materials and in anthropogenic emissions are often very different (see Komárek et al 2008 for a complete review) allowing the sources and pathways of metal pollution to be more clearly identified (Carignan and Gariépy 1995;Monna et al 1999;Getty et al 1999;Doucet and Carignan 2001;Carignan et al 2002;Simonetti et al 2003;Watmough and Hutchinson 2004;Spiro et al 2004;Cloquet et al 2006;Farmer et al 2010). …”
Section: Introductionmentioning
confidence: 99%
“…However, from a political and sociological perspective, large-scale closure of operations is currently impossible as mining industries are major employers underpinning the economy of the region. There have been several studies on the nature and environmental effects of atmospheric pollution in and around Karabash (Voskresensky 2002;Spiro et al 2004;Williamson, Mikhailova, et al 2008;Williamson et al 2008). Lichens were found to contain particulate from the smelter for a distance of up to 30 km.…”
Section: Study Areamentioning
confidence: 99%